Police are Influenced by Anchoring and Risk When Allocating Resources for Scenario-based Intimate Partner Violence Cases - Kebbell, Mark R. (Journal of interpersonal violence, 2022)
Sixty-six police officers were given four intimate partner violence (IPV) scenarios to rate for risk of future violence. At the start of the experiment, participants were provided with either a low-risk or high-risk ?anchor? scenario of police attending an IPV incident. Next, participants were given three counterbalanced scenarios: high, medium, and low risk. Half the participants were given a structured professional judgment tool to guide their decisions. Participants given the low-risk anchor rated the following scenarios as being of greater risk than those given the high-risk anchor. Participants were consistent in identifying high-, medium-, and low-risk scenarios and the tool made no difference to these ratings. Participants were more confident in their higher risk judgments than their lower risk judgments. Officers distributed a disproportionately high amount of resources to the high-risk offenders and the results suggest that police officers can make decisions consistent with Risk-Need-Responsivity principles. However, anchoring effects and working in a context where violence is more severe and frequent has the potential to bias perceptions and make officers less sensitive to risk.